Improving quality in coffee chains in Papua New Guinea - Murray-Prior, Roy; Batt, Peter; Dambui, C.; Kufinale, K. (ISHS, 2007)
In PNG, coffee that achieves A grade, Organic or Fair Trade certification sells at a considerable premium to the NY 'C'. Unfortunately, only about 10 percent achieves this status, while 80 percent is Y grade coffee. The key reason for this difference in price, which is around 30-40 US c/lb, is poor processing at the village level, leading to inconsistent product quality. A number of chains have overcome this problem by improving quality through: (i) purchasing cherry from smallholder and blockholder farmers and processing the coffee in centralised wet mills owned by plantations and exporters to produce speciality coffee; (ii) delivering coffee to accredited organic and Fair Trade markets; or (iii) various projects sponsored by individual exporters, the Coffee Industry Corporation and international donors that provide smallholder collaborative groups with training in agronomy, processing and marketing to produce better quality parchment. While both options seek to achieve higher prices through improving quality, the first two options seek to move the coffee produced from the soluble coffee market to the speciality market where much higher premiums are potentially available. The advantages and disadvantages of these options are discussed and conclusions are reached about the likelihood of each being successful in the long run.